Moonwalking with Einstein : the art and science of remembering everything - Foer, Joshua (Penguin Press, 2011)
Having achieved the seemingly unachievable-- becoming a U.S. Memory Champion-- Foer shows how anyone with enough training and determination can achieve mastery of their memory.